2020
DOI: 10.3390/s20072095
|View full text |Cite
|
Sign up to set email alerts
|

Gait Characteristics Based on Shoe-Type Inertial Measurement Units in Healthy Young Adults during Treadmill Walking

Abstract: This study investigated the gait characteristics of healthy young adults using shoe-type inertial measurement units (IMU) during treadmill walking. A total of 1478 participants were tested. Principal component analyses (PCA) were conducted to determine which principal components (PCs) best defined the characteristics of healthy young adults. A non-hierarchical cluster analysis was conducted to evaluate the essential gait ability, according to the results of the PC1 score. One-way repeated analysis of variance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…Finally, our walking tasks at the slower, preferred, and faster speed conditions were conducted on a treadmill for a duration of 1 min, which is useful for collecting numerous continuous walking steps [ 58 ]. However, treadmill walking tasks may indicate relatively less GV values compared with overground walking, according to the task characteristics, because the walking speed on the treadmill imposes a steady speed condition, which minimizes the variance of the step compared with overground walking [ 38 ]. In addition, the treadmill walking speed acts as an external cue for the participants [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, our walking tasks at the slower, preferred, and faster speed conditions were conducted on a treadmill for a duration of 1 min, which is useful for collecting numerous continuous walking steps [ 58 ]. However, treadmill walking tasks may indicate relatively less GV values compared with overground walking, according to the task characteristics, because the walking speed on the treadmill imposes a steady speed condition, which minimizes the variance of the step compared with overground walking [ 38 ]. In addition, the treadmill walking speed acts as an external cue for the participants [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the treadmill walking test, the participants were asked to walk to maintain a stable walking pattern for each speed condition on the treadmill for about 30–60 s at the onset of the treadmill walking. An operator collected the treadmill walking data at 100 Hz (1-min periods) when a participant attained a stable walking pattern [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Some previous studies have reported that treadmill gait exhibits similar patterns to over-ground gait [ 23 , 24 , 25 , 26 ]. Therefore, multiple continuous steps of gait analysis for healthy people with treadmill experience may provide reliable and objective data [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…These patterns may be one of the symptoms of declining gait stability in the low TFMS group. The GV value is decreased with increasing walking speed due to enhanced dynamic stability during walking ( Lee et al, 2020c ). In addition, control of the walking-related rhythmic stepping mechanism is reflected by stride-to-stride variability ( Gabell & Nayak, 1984 ), and the lower variability reflects automatic processes that require minimal attention, which can be attributed to efficient gait control and stability ( Hausdorff et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…During the treadmill walking test, the participants were asked to walk while maintaining a stable walking pattern for each speed condition on the treadmill for approximately 30–60 s at the onset of treadmill walking. An operator collected the treadmill walking data at 100 Hz (1 min periods) when a participant attained a stable walking pattern ( Lee et al, 2020c ). The treadmill walking procedure followed this sequence: (1) self-preferred speed; (2) faster speed; (3) slower speed.…”
Section: Methodsmentioning
confidence: 99%